Performance analysis of physical layer security over α–μ fading channel. Issue 1 (1st January 2016) - Kong, L.; Tran, H.; Kaddoum, G.
Abstract : Recently, many works have focused on analysing the metrics of physical layer security over different wireless channels such as additive white Gaussian noise, Rayleigh, Rician and Nakagami‐ m fading distributions. To extend the analysis to the general case, the α – μ fading channel is considered, which can span the aforementioned cases. For this purpose, the physical layer security over the α – μ fading channel is presented. The closed‐form expressions for the probability of positive secrecy capacity and upper bound of the secrecy outage probability are derived. Their accuracies are assessed through comparison of theoretical analysis and simulations results.